Minimally invasive mitral valve surgery after failed transcatheter mitral valve repair in an intermediate-risk cohort. (17th June 2022) - Akansel, Serdar; Kofler, Markus; Van Praet, Karel M; Unbehaun, Axel; Sündermann, Simon H; Jacobs, Stephan; Falk, Volkmar; Kempfert, Jörg
Abstract: OBJECTIVES: Although clinical experience with transcatheter mitral valve interventions is rapidly increasing, there is still a lack of evidence regarding surgical treatment options for the management of recurrent mitral regurgitation (MR). This study provides guidance for a minimally invasive surgical approach following failed transcatheter mitral valve repair, which is based on the underlying mitral valve (MV) pathology and the type of intervention. METHODS: A total of 46 patients who underwent minimally invasive MV surgery due to recurrent or residual MR after transcatheter edge-to-edge repair or direct interventional annuloplasty between October 2014 and March 2021 were included. RESULTS: The median age of the patients was 78 [interquartile range, 71–82] years and the EuroSCORE II was 4.41 [interquartile range, 2.66–6.55]. At the index procedure, edge-to-edge repair had been performed in 45 (97.8%) patients and direct annuloplasty in 1 patient. All patients with functional MR at the index procedure (n = 36) underwent MV replacement. Of the patients with degenerative MR (n = 10), 5 patients were eligible for MV repair after removal of the MitraClip. The 1-year survival following surgical treatment was 81.3% and 75.0% in patients with functional and degenerative MR, respectively. No residual MR greater than mild during follow-up was observed in patients who underwent MV repair. CONCLUSIONS: Minimally invasive surgery following failed transcatheter mitral valve repair is feasible and safe, with promising midterm survival. The surgical management should be tailored to the underlying valve pathology at the index procedure, the extent of damage of the MV leaflets and the type of previous intervention. Abstract : Transcatheter mitral valve repair (TMVr) has evolved as an alternative therapeutic option to mitral valve surgery for high surgical risk or inoperable patients suffering from mitral regurgitation (MR).